Exploring Customer Relationship Management: Trends, Challenges, and Innovations - Erick Fernando; Rudi Sutomo; Yulius Denny Prabowo; Jullend Gatc; Winanti Winanti (Journal of Information System and Informatics, 2023)
This study presents a comprehensive exploration of recent advancements in Customer Relationship Management (CRM), acknowledging its pivotal role in fostering crucial connections both within the industry and with customers at large. The study delves deeply into CRM, aiming to enhance overall customer satisfaction. The primary focus of this study centers around critical facets of CRM, encompassing strategies for managing customer relationships, applications of information technology, analysis of customer data, and approaches for customer retention. Employing a literature review methodology, this research rigorously examines the most recent journals germane to the field of CRM. A total of 46 articles sourced from reputable journal databases constitute the foundation of this investigation. The findings of this study yield an enriched comprehension of contemporary developments concerning challenges, factors driving success, relevant domains, and implementation goals within the realm of Customer Relationship Management.